The practice of peer assessment in primary school. A systematic literature review - Stecca, Eleonora; Grion, Valentina; Zaggia, Cristina; Restiglian, Emilia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2022)
While in higher education and secondary school, there are already a lot of experiences and models of applying peer assessment, there are still few research attempts regarding this method of assessment for learning in primary school. This study consists of a systematic review of the literature conducted to investigate the practice of peer assessment applied to primary school. The evidence highlights the methods of applying peer assessment with primary school pupils and the benefits reached in the contexts involved.